О ТРОФИЧЕСКОМ СТАТУСЕ ПЕЛАГИЧЕСКИХ ЭКОСИСТЕМ В РАЗНЫХ РЕГИОНАХ ЧЕРНОГО МОРЯ - Заика, В. Е. (Marine Ecological Journal, 2023)
The review concentrates on the definitions and terminology related to eutrophication of pelagic zone of the sea and compares between characteristics describing trophic status of a water area. Since the mid-20-th century, trophic status of deep-water areas of the Black Sea had been changing from oligo-mesotrophic to meso-eutrophic, and by the Late 1980-s some coastal and estuarine localities were defined as hypertrophic. Since 1992, the marine environment has been ameliorating and the trophic level declining. Special emphasis is placed on that trophic status should be assessed for each area of the sea separately.